PENINGKATAN KETERAMPILAN BERBICARA BAHASA INGGRIS DENGAN MEDIA PERMAIAN ULARTANGGA - Wahya, I Ketut (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2011)
According to the Curriculum Based Competency, the objective of learning English is to master the communication competence, it means that the students should be able to express their idea and their feeling in communication activities even in oral or in written. So, English teacher should be able to assist their students to become effective participants in real life communication. We need to help them in any ways that motivate them to use the language as many times as possible. The main goal of teaching English to the secondary school is to developed their language skills; listening, speaking, reading and writing. Based on experience as English teacher at secondary school (SMP Negeri 1 Bangli), most students still poor using the language in communication even in oral or in written. This problem appear because of some factors like; lack of vocabulary, poor in grammar, lack of practicing use the language, and boring because the teacher’s strategy in teaching is monotone, and never use media. To solve those problems, the writer try to do the Classroom Action Research. The research focus on developing speaking skill using media Snake and Ledger game.